Short-Term Outcome of Patients in Delirium at Medical Intensive Care Unit - Khatri, Roshni; Dhungana, Saraswati; Ojha, Saroj Prasad; Khatri, Sushila; Khadka, Santosh; K.C., Prakash (Journal of Nepal Health Research Council, 2024)
Background: Delirium is highly prevalent in the Intensive Care Unit (ICU), and managing it in critically ill patients with severe comorbidities is challenging due to transient nature of symptoms. However its significance is underestimated, often overlooked and misdiagnosed by healthcare providers. In Nepal, limited studies has been done on delirium in medical ICUs hence this study aims to assess short-term outcome of admitted patients in delirium. Methods: Descriptive cross-sectional observational study was conducted among 92 patients referred from medical ICU with history of disorientation and altered sensorium, assessed during consultation liaison and meeting the criteria for delirium. Data were collected using semi-structured proforma. Richmond Agitation Sedation Scale and Delirium Rating Scale-Revised 98 were used to know the pattern and severity of delirium at day 0 and seven respectively and phone follow-up was done at three months. Data were tabulated and analyzed using SPSS version 25.0. Results: Hyperactive delirium (57.6%) was most common in medical ICU. Out of total patients, 63.2% improved, 23% became worse and 13.8% remain static with treatment. Mean length of hospital stay was 11.1 days. Hypoactive delirium was associated with longer hospital stay and increased mortality. Significant association was found between length of ICU stay and outcome in terms of mortality and response to treatment. Conclusions: Study underscores the prevalence of hyperactive delirium as the predominant pattern in MICU settings. However, it is crucial to highlight the significance of hypoactive delirium due to its poor treatment response and prolonged ICU stays compared to other forms. Keywords: Delirium; length of ICU stay; mortality pattern; outcome.